An Analysis of Tourism Promotion Strategies: Enhancing Destination Competitiveness through Creative - Mulyana, Hadi (PT. Hafasy Dwi Nawasena, 2025)
This article analyzes tourism promotion strategies by focusing on the role of creative marketing in enhancing destination competitiveness. The rapid development of digital technology has shifted promotional efforts from conventional models to more participatory, story-driven, and community-based approaches. Employing a qualitative-descriptive method with a case study design, this study draws on data collected from key tourism destinations in Indonesia, including Pangandaran, Labuan Bajo, and Nglanggeran Village. Data analysis followed a thematic approach using manual coding to identify patterns in promotional practices and community engagement. Findings reveal that active participation of local communities particularly MSMEs as digital content creators significantly expands promotional reach while strengthening cultural identity and local economic resilience. The integration of the PESO model (Paid, Earned, Shared, Owned) with digital storytelling, user-generated content (UGC), and cross-stakeholder collaboration contributes to building a distinctive and emotionally resonant destination image. This study contributes to the theoretical discourse on tourism marketing by offering an integrative framework that connects digital creative strategies with grassroots promotional dynamics, providing new insights into sustainable and community-embedded tourism branding.